2012
DOI: 10.1038/bjc.2012.240
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of ethnic minorities into cancer clinical trials: experience from the front lines

Abstract: Throughout the world there are problems recruiting ethnic minority patients into cancer clinical trials. A major barrier to trial entry may be distrust of research and the medical system. This may be compounded by the regulatory framework governing research with an emphasis on written consent, closed questions and consent documentation, as well as fiscal issues. The Leicester UK experience is that trial accrual is better if British South Asian patients are approached by a senior doctor rather than someone of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 28 publications
0
80
0
Order By: Relevance
“…Cultural and languagebarriers have often been implicated as reason for low recruitment and poor retention of cancer participants (Ford et al, 2008;Gul and Ali, 2010;Symonds et al, 2012 our Qigong trial, language was not the major barrier but cultural issues may well be a key contributor to the attrition rate as we observed a pattern in the different ethnic groups. A recent study by Hui and colleagues (2012) showed that high cancer patients attrition were associated with various patient characteristics and a high baseline symptom burden such as dyspnea (OR, 1.06; p=0.01), fatigue (OR, 1.08; p=0.01), Hispanic race (OR, 1.87; p=0.002), higher level of education (p=0.02), longer study duration (p=0.01), and outpatient studies (p=0.05).…”
Section: Discussionmentioning
confidence: 64%
“…Cultural and languagebarriers have often been implicated as reason for low recruitment and poor retention of cancer participants (Ford et al, 2008;Gul and Ali, 2010;Symonds et al, 2012 our Qigong trial, language was not the major barrier but cultural issues may well be a key contributor to the attrition rate as we observed a pattern in the different ethnic groups. A recent study by Hui and colleagues (2012) showed that high cancer patients attrition were associated with various patient characteristics and a high baseline symptom burden such as dyspnea (OR, 1.06; p=0.01), fatigue (OR, 1.08; p=0.01), Hispanic race (OR, 1.87; p=0.002), higher level of education (p=0.02), longer study duration (p=0.01), and outpatient studies (p=0.05).…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, there may be no direct equivalent of technical words. For instance, there is no word for cancer in Hindi and Gujarati and no acceptable term for breast cancer (Symonds et al, 2012). Equally, the words 'palliative care' and 'terminal care' do not translate directly into most non-European languages.…”
Section: Discussionmentioning
confidence: 99%
“…However, recommendations are lacking for optimal recruitment from different ethnic minority groups in Australia, as well as for the recruitment of multi-generational family units from different ethnic backgrounds into the same trial. Moreover, despite the growing focus on the challenges associated with recruitment from ethnic minority groups, under-representation remains a problem [15,16,31].…”
Section: Introductionmentioning
confidence: 98%